KUALITAS PELAYANAN PEMBUATAN DOKUMEN AKTA KELAHIRAN DALAM MEWUJUDKAN PELAYANAN PRIMA PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN INDRAMAYU - Ahmad Ramdoni; Hery Nariyah; RM Haryo Bharoto (Universitas Swadaya Gunung Jati, 2015)
ABSTRACT Problems experienced by the community towards the services provided by the government often make people disappointed. So that people often feel lazy in dealing with service personnel. So it has become a habit of the people not to take care of their service needs directly. Communities often tell others to take care of their needs with government agencies both in the District and other technical services. Of course, this makes a common concern and must be able to tap the awareness of the trustees who work in public service agencies to improve the service to the community as well as possible.The identification of the problems raised in this study are as follows: What is the quality of service for making birth certificates at the Indramayu Regency Population and Civil Registration Service, what obstacles are faced in providing services for the birth certificate at the Indramayu Regency Population and Civil Registration Service? what efforts have been made in overcoming barriers to service in making birth certificates at the Indramayu Regency Population and Civil Registration Service?Based on the background and identification of the problem above, the writer takes the title in this study, namely the Quality of Service for Making Birth Certificate in Realizing Excellent Service in the Department of Population and Civil Registration, Indramayu Regency. The research method that I use is a qualitative method with a descriptive approach in analyzing the data can obtain real information and be able to study the research more deeply so that the data and information obtained are expected to be accurate.The quality of service for making birth certificates at the Department of Population and Civil Registry is still not maximal. This is because there are still many problems in the service process as well as the time in completing the creation of a birth certificate and limited human resources (HR), this limited human resource causes less than optimal service. Technical and non-technical problems faced in providing services for making birth certificates to the community such as the number of applicants for birth certificates that will make birth certificates but employees who do them or handle them inadequately, often jammed computers that are used for typing and operating data such as viruses or other things that inevitably have to be serviced first before being reused. Efforts are made in an effort to improve the quality of service for making birth certificates such as adding the number of computer units, conducting socializations to communities in the regions (Village and District) both directly and indirectly.